Booming provincial-led North–South City-to-city cooperation in China: A case study of Suzhou-Suqian Industrial Park of Jiangsu Province. (August 2015) - Xian, Shi; Chan, Roger C.K.; Qi, Zhixin
Highlights: Focus on North–South City-to-city (C2C) cooperation led by the provincial government in China. Reject an absolute distinction between opposite arguments of the role of provincial government. Reveal a diverse trend in goals and approaches adopted by China's provincial government. Balance between market power and government power varies in different stages of the cooperation. Abstract: China has undergone economic and political restructuring in the post-socialist era under the background of globalization. At the same time, its provincial governments have mobilized various forms of booming North–South City-to-city (C2C) cooperation within their respective jurisdictions during the last ten years. This paper investigates the dynamics behind such cooperation through a case study of the Suzhou-Suqian Industrial Park in Jiangsu, with the aim of enriching and diversifying debates about the changing roles and functions of China's provincial government and introduction of market in the North–South C2C cooperation. Several scholars argued that the roles and functions of the provincial government have weakened with China's neoliberal shifts, whereas others insist that they have maintained a strong role in local governance. The findings of this study do not support an absolute distinction between these two sides. A diverse trend is identified when look into this argument in terms of goals and approaches. It is found that the regulation power of provincial government continues to have strong goals, but its approaches are changing from a direct to a market-oriented one. The debate about the balance between market power and government intervention under China's context has been receiving attention as well. It is found that in discussing which driving force is more important in the local cooperation programme, the conclusion varies in different stages of the cooperation process. Results support the importance of introducing market in the North–South C2C development cooperation under China's context. Although the booming North–South City-to-city cooperation mobilized by China's provincial government is derived from the national slogan of reducing regional disparity, local governments are also seizing the opportunity and using the top-down scheme to solve local development bottlenecks and crises as well as to reposition the jurisdictions amidst the yardstick competition. Such cooperation prevents interprovincial industrial relocation to a certain extent; thus, it has considerable influence on China's industrial transfer paths and its economic restructuring pattern.